An Exploration of ethnomthematics in the Cibuntu Tofu industry - hakim, Fahril; Fitria, Nury Ainun; Nurlaela, Siti; Putra, Harry Dwi (Pi Radian: Journal of Mathematics Education, 2024)
Ethnomatematics is a science that studies or unites culture with mathematics. Culture is a habit of the people that is often carried out every day and Mathematics has many benefits for human life, so without realizing it, many mathematical concepts are applied in everyday life. Like calculating sizes and drawing a plane shape, buying and selling transactions are related to integer operations. This is in line with the research conducted, namely studying and analyzing ethnomathematics exploration in making tofu in Cibuntu which is a daily livelihood in order to obtain basic information in developing ethnomathematics for learning mathematics in the field of geometry specifically on the shape and size of tofu and learning mathematics in the field of social arithmetic specifically in tofu price. The goal in making Ethnomathematics is to harmonize the culture of the Cibuntu residents into the concept of Mathematics. The method used in this study is the Exploration method, which is to search in depth about Cibuntu Tofu. The instruments used in this study were interviews and documentation.